New directions for organization theory problems and prospects - Pfeffer, Jeffrey (Oxford Univ. Press, 1997)
Pfeffer argues that the world of organizations has changed in several important ways, including the increasing externalization of employment and the growing use of contingent workers; the changing size distribution of organizations, with a larger proportion of smaller organizations; the increasing influence of external capital markets on organizational decision-making and a concomitant decrease in managerial autonomy; and increasing salary inequality within organizations in the US compared both to the past and to other industrialized nations. These changes and their public policy implications make it especially important to understand organizations as social entities. But Pfeffer questions whether the research literature of organization studies has either addressed these changes and their causes or made much of a contribution to the discussion of public policy
Keywords: Comportement organisationnel; Conducta organizacional; Control social; Contrôle social; Organisatiegedrag; Organisatiesociologie; Sociologie des organisations; Organizational sociology; Organizational behavior; Social control; Organisationssoziologie; Organisationstheorie; Organisationsverhalten